2023
DOI: 10.13004/kjnt.2023.19.e54
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Traumatic and Non-Traumatic Spinal Cord Injury in Korea: A Narrative Review

Yoonjeong Choi,
Ja-Ho Leigh

Abstract: This review describes the incidence rates and trends of traumatic spinal cord injuries (TSCI) and non-traumatic spinal cord injuries (NTSCI) in South Korea. The incidence of NTSCI has increased more rapidly than that of TSCI in recent years. In 2007, TSCI was more common, but by 2020, NTSCI had surpassed TSCI, particularly in older individuals. While men have a higher incidence of both TSCI and NTSCI, the incidence difference by sex is greater in TSCI. The incidence rates of both TSCI and NTSCI are higher in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Cervical SCIs are the most common TSCI, especially in high-income countries like South Korea. 13 Current published literatures and systematic reviews demonstrated limitations and it is di cult to acquire accurate epidemiological data for TSCI in Asia. 14 Despite a growing body of literature about spine disorders, we found several limitations of Asian epidemiology due to the scarcity of population based published data.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical SCIs are the most common TSCI, especially in high-income countries like South Korea. 13 Current published literatures and systematic reviews demonstrated limitations and it is di cult to acquire accurate epidemiological data for TSCI in Asia. 14 Despite a growing body of literature about spine disorders, we found several limitations of Asian epidemiology due to the scarcity of population based published data.…”
Section: Introductionmentioning
confidence: 99%